La représentation de la musique et de la danse dans les œuvres de Post et Wagner : une archéologie des musiques noires au Brésil - Jean-Pierre Estival (Journal de la Société des Américanistes)
The relatively brief period of Dutch colonization in Pernambuco (1630-1654) corresponds to an exceptional documentary undertaking driven by Jean-Maurice de Nassau. Frans Janzsoon Post, responsible for the painting of landscapes, villages and their inhabitants, often represented Black drummers accompanied by a few dancers. Here, we attempt to define a recurrent motif in the corpus of these works, belonging to the Dutch Golden Age. A gouache from the adventurer Zacharias Wagner completes the collection. By comparing art history analysis concerning the place of music in contemporary Dutch paintings with the few written sources, we emphasize the following points: precision regarding the organologic descriptions, the position of the musicians and the dancers’ bodies, as well as the type of performance represented.